2007
DOI: 10.1093/ndt/gfm715
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt ameliorates renal injury in an obese, hypertensive type 2 diabetes rat model

Abstract: Cobalt achieved renal protection independently of metabolic status and blood pressure. Its effect was attributed to the upregulation of HIF and HIF-regulated genes and to a mitigated advanced glycation and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 31 publications
10
106
2
Order By: Relevance
“…25 The finding that chronic HIF activation reduced proteinuria is in line with previous studies. Song et al 26 recently showed that HIF activation halted progression of proteinuria in a 27 reported that HIF activation by cobalt reduced renal expressions of TGF-b, connective tissue growth factor, and NADPH oxidase as well as reduced proteinuria, tubulointerstitial damage, and peritubular capillary loss in experimental type 2 diabetes. Indeed, tubulointerstitial fibrosis is a reliable marker for progression of kidney disease, and it is, therefore, interesting that HIF activation ameliorated fibrosis development in the diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The finding that chronic HIF activation reduced proteinuria is in line with previous studies. Song et al 26 recently showed that HIF activation halted progression of proteinuria in a 27 reported that HIF activation by cobalt reduced renal expressions of TGF-b, connective tissue growth factor, and NADPH oxidase as well as reduced proteinuria, tubulointerstitial damage, and peritubular capillary loss in experimental type 2 diabetes. Indeed, tubulointerstitial fibrosis is a reliable marker for progression of kidney disease, and it is, therefore, interesting that HIF activation ameliorated fibrosis development in the diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were The control and STZ-injected animals were randomly divided into receiving either vehicle or CoCl 2 (20 mgzkg body wt 21 per 24 hours 21 ) in the drinking water for the entire duration of diabetes. 27 A detailed schematic drawing of the experimental design is depicted in Figure 9.…”
Section: Animals Induction Of Diabetes and Chronic Treatmentmentioning
confidence: 99%
“…This is of significant clinical relevance. Because cobalt has been under development as a drug to promote HIF-1 transcriptional activity (Endoh et al, 2000;Ohtomo et al, 2008), factors affecting its efficacy and long-term safety have to be considered. It is reasonable to consider the use of cobalt to promote angiogenesis in ischemic tissues.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The mechanism of action of cobalt involves the inhibition of prolyl hydroxylases (Yuan et al, 2003;Maxwell and Salnikow, 2004;Hirsila et al, 2005;Ke et al, 2005). Because of the pivotal role of HIF-1 in multiple cellular function and homeostasis, cobalt has been extensively studied for its potential as a drug to stimulate cellular function regulated by HIF-1 (Endoh et al, 2000;Ohtomo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of HIF-1␣ by CoCl 2 ameliorates the renal injury in rats with nephritis (60) and hypertensive type 2 diabetes (46). In contrast to the deleterious effects of overexpressed HIF-1␣ in 5 ⁄6 nephrectomy mice (23), other reports have shown that upregulation of HIF-1␣ by pharmacological agents protects the kidneys using the same 5 ⁄6 nephrectomy model of CKD (6,56,59).…”
mentioning
confidence: 98%